ChemInform Abstract: Recent Advances in Highly Selective Applications of Nitroso Compounds. Issue 40 (September 2016) - Huang, Jiapian; Chen, Zhiyuan; Yuan, Jianjun; Peng, Yiyuan
Abstract: Review: [application of nitroso derivatives in heterocyclization and direct C—H functionalization reactions; 58 refs.